Sirtuin 1 Is a Negative Regulator of Parathyroid Hormone Stimulation of Matrix Metalloproteinase 13 Expression in Osteoblastic Cells: ROLE OF SIRTUIN 1 IN THE ACTION OF PTH ON OSTEOBLASTS - Fei, Yurong (J Biol Chem, 2015)
Parathyroid hormone (PTH) is the only current anabolic treatment for osteoporosis in the United States. PTH stimulates expression of matrix metalloproteinase 13 (MMP13) in bone. Sirtuin 1 (SIRT1), an NAD-dependent deacetylase, participates in a variety of human diseases. Here we identify a role for SIRT1 in the action of PTH in osteoblasts. We observed increased Mmp13 mRNA expression and protein levels in bone from Sirt1 knock-out mice compared with wild type mice. PTH-induced Mmp13 expression was significantly blocked by the SIRT1 activator, resveratrol, in osteoblastic UMR 106-01 cells. In contrast, the SIRT1 inhibitor, EX527, significantly enhanced PTH-induced Mmp13 expression. Two h of PTH treatment augmented SIRT1 association with c-Jun, a component of the transcription factor complex, activator protein 1 (AP-1), and promoted SIRT1 association with the AP-1 site of the Mmp13 promoter. This binding was further increased by resveratrol, implicating SIRT1 as a feedback inhibitor regulating Mmp13 transcription. The AP-1 site of the Mmp13 promoter is required for PTH stimulation of Mmp13 transcriptional activity. When the AP-1 site was mutated, EX527 was unable to increase PTH-stimulated Mmp13 promoter activity, indicating a role for the AP-1 site in SIRT1 inhibition. We further showed that SIRT1 deacetylates c-Jun and that the cAMP pathway participates in this deacetylation process. These data indicate that SIRT1 is a negative regulator of MMP13 expression, SIRT1 activation inhibits PTH stimulation of Mmp13 expression, and this regulation is mediated by SIRT1 association with c-Jun at the AP-1 site of the Mmp13 promoter.